PENGEMBANGAN PEMBELAJARAN BERBASIS PROYEK DENGAN CANVA YANG DIINTERNALISASI MODERASI BERAGAMA - Eka Lutfiyatun; Rifda Haniefa; Khabib Syaikhu Rohman (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
Religious moderation is urgent for Indonesian Muslims. Although independent curriculum emphasizes project-based learning (PjBL), learning is only provided as material and not integrated with projects to optimize competence and creativity. This research aims to find out the form of PjBL using Canva internalized with religious moderation, its validity, and its effectiveness. It is research and Development with mixed methods through tests, questionnaires, and observations. The subjects were 8th grade students at SMP Nurussalam Depok. The results are the stages of PjBL for Islamic Education with Canva internalized with religious moderation, namely pre-project, project implementation, and post-project. Religious moderation practiced was tolerance, such as respecting others, accepting differences, honoring others, and not forcing others to have the same thinking and acting. Students created posters about tolerance. The product validation is 89.49 (very feasible). The posttest score is better than the pretest (91.20). Students practiced religious moderation values very well, especially tolerance.